Analisis Kegiatan Kewirausahaan Untuk Memotivasi Masyarakat Desa Mudung Darat Dalam Meningkatkan Pertumbuhan Ekonomi Desa - Isnaini Isnaini; Redi Indra Yudha (SJEE (Scientific Journals of Economic Education), 2023)
This research aims to find out why the community has not been encouraged to increase theirentrepreneurial potential in increasing economic growth in Mudung Darat village. This type of research usesqualitative research. Meanwhile, the technique in this research uses the cluster sampling technique to determinewhen the object to be researched or the data source is very extensive. The result of the research show that theencouragement given from various parties allows people to change their thinking to be encouraged to becomeentrepreneurs in increasing the growth of a more prosperous life for the survival of every existing community.Thus, people have not been encouraged to increase their entrepreneurial potential in increasing villageeconomic growth because people open business basically because of hobbies where people are less interested inentrepreneurship.